PENGEMBANGAN MORAL ANAK USIA DINI DALAM MEMBENTUK ETIKA WIRAUSAHA - Leonita Siwiyanti (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2016)
Corruption and honesty become a rare item and hard to find. And the key to the success of a company is their honesty enforced by truly sunggh. This causes the importance of ethics in entrepreneurship, so that the application and development of early moral indispensable. Where early childhood is the foundation early in the formation of ethics as a whole, particularly the entrepreneurial ethic. So that habituation and moral development of early childhood, such as: honesty, discipline, confidence, and leadership can be established early on. In the moral development for early childhood needs to be done very carefully. This is because early childhood is children who are in the stage of development of pre-operational concrete, while moral values are concepts that are abstract, so that in this case the children are not able to necessarily accept what is taught by teacher / parent is abstract rapidly. For that "old man" must be clever to choose and determine the methods used to inculcate moral values to children. Ceenderung storytelling method is more widely used, because early childhood is usually happy when listening to stories from parents / teachers. One of the stories that match the entrepreneurial ethic is the paragon of our Prophet Muhammad.